Laterality-specific training improves mental rotation performance in young soccer players - Pietsch, S.; Jansen, P. (Frontiers in Psychology, 2018)
This study investigates the influence of specific soccer training with the non-dominant leg on mental rotation performance of 20 adolescent soccer players between 10 and 11 years of age. While the experimental group performed soccer specific tasks only with the non-dominant foot once a week for 10 weeks, the control group absolved the same exercises with the dominant foot for the same period of time. Both groups performed a mental rotation task and shot, dribbling and ball control tests before and after the 10 week intervention. The most relevant result was that the experimental group showed a significantly larger increase in mental rotation ability than the control group.